2015
DOI: 10.5424/fs/2015241-05887
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of shrub diversity and tree regeneration across topographic and stand-structural gradients in a Mediterranean forest

Abstract: Aim of study: This study aimed to determine the influence of topography and stand-structure on the characteristics of shrub communities and tree regeneration in a Mediterranean forest.Area of study: The Navahondona forest in Cazorla mountain range (SE Spain).Material and Methods: Data from 298 inventory plots were analysed by means of Generalized Linear Models (GLM) to test the effects of aspect, altitude and stand basal area on shrub cover and diversity. Likewise, the effects of these three factors plus shrub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 41 publications
2
10
0
Order By: Relevance
“…Basal area (G) affected Q. suber regeneration positively, in agreement with other studies where a nursing effect of tree cover was reported [39,100]. It is striking to note that Q. suber was the only taxon for which saplings density did not increase with the density of stands dominated or co-dominated by Q. suber adult trees in the neighbourhood (SeedAvail).…”
Section: Q Subersupporting
confidence: 89%
“…Basal area (G) affected Q. suber regeneration positively, in agreement with other studies where a nursing effect of tree cover was reported [39,100]. It is striking to note that Q. suber was the only taxon for which saplings density did not increase with the density of stands dominated or co-dominated by Q. suber adult trees in the neighbourhood (SeedAvail).…”
Section: Q Subersupporting
confidence: 89%
“…Grazing, especially from wild ungulates, is among the main threats for most populations, both for species and habitat. Overgrazing by domestic and wild ungulates (García-González & Cuartas, 1989;Soriguer et al, 2003), affecting significantly the structure, composition and regeneration of the vegetation (Tíscar-Oliver, 2015). It was also the main threat factor in many endangered species and acted synergistically with other threat factors (Lorite et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The total amount of vascular plants accounted for the area is 2,200, with 360 endemics to the Baetic-Rifan complex, 35 of them being narrow endemics of these mountains (Benavente, 2005). This mountain range has typically been overgrazed by domestic and wild ungulates (García-González & Cuartas, 1989;Soriguer et al, 2003), affecting significantly the structure, composition, and regeneration of the vegetation (Tíscar-Oliver, 2015). It is the main threat factor in the area acting synergistically with other threat factors such as climatic change, land use changes, or forestry (Lorite et al, 2007;Heywood, 2014).…”
Section: Study Sitementioning
confidence: 99%
“…, Harper et al. , Tiscar‐oliver ). That said, further study is required to differentiate whether seedlings are responding to differences in environmental conditions or to the influence of shrubs, which are themselves responding to the environment.…”
Section: Discussionmentioning
confidence: 99%